PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN BAKSO SAM CIPONDOH PADA CV. SURYA ARTHA MUTIARA CIPONDOH, DI KOTA TANGERANG - Muhammad Mahudi; Reza Khairul Hadi (Jurnal Manajemen & Pendidikan [JUMANDIK], 2025)
This istudy iaims ito idetermine ihow imuch iinfluence ipromotion iand iservice iquality ihave ion ipurchasing idecisions ifor iSAM iCipondoh imeatballs iat iCV.Surya iArtha iMutiara iCipondoh, iIn iTangerang iCity. iused iis ia iquantitative imethod. iThe isampling itechnique iused iis inon-probability isampling iusing ithe iChocran iformula, inamely ithe inumber iof isamples iis i99 irespondents. iThe idata ianalysis iused iis ivalidity itest, ireliability itest, isimple ilinear iregression, icorrelation icoefficient, idetermination icoefficient, iand ihypothesis itesting. iThe iresults iof ithis istudy iare ithe imoderate ieffect iof ipromotion i(XI) iand iservice iquality i(X2) ion ipurchasing idecisions i(Y) iat ithe iCV.Surya iArtha iMutiara iCipondoh, iTangerang. iPromotion iwith iregression iY i= i16.974 i+ i0.695X1, ithe icorrelation icoefficient ivalue iis i0.629 imeaning ithat ithe itwo ivariables ihave ia imoderate irelationship iwith ia idetermination icoefficient iof i39.6% iand ithe ihypothesis itest iis iobtained it icount i> it itable i(7.967 i> i1.98498). iService iquality ihas ia isignificant iinfluence ion ipurchasing idecisions iwith ithe iregression iequation iY i= i22.907 i+ i0.386X2, ithe icorrelation icoefficient ivalue iis i0.447 imeaning ithat ithe itwo ihave ia ilow irelationship iwith ia icoefficient iof idetermination iof i20% iand ihypothesis itesting iobtained it icount i> it itable i(4.927 i> i1.98498). iPromotion iand iservice iquality isimultaneously ihave ia isignificant ieffect ion iPurchasing iDecisions iwith ithe iregression iequation iY i= i13.801 i+ i0.597X1 i+ i0.155X2. iValue icorrelation icoefficient iobtained iby i0.648 imeans ithat ithe iindependent ivariable iwith ithe idependent ivariable ihas ia imoderate irelationship iwith ia idetermination icoefficient iof i42% iwhile ithe irest iis ias ibig ias iinfluenced iby iother ifactors. iHypothesis itesting iobtained iFcount i> iFtable ior i(34.761 i> i3.090). iThis iis ialso ireinforced iby ithe isignificance iprobability iof i0.000 i<0.05. iThus iH0 iis irejected iand iH1 iis iaccepted. iThis imeans ithat ithere iis ia ipositive iand isignificant iinfluence isimultaneously ibetween ipromotion iand iservice iquality ihave ion ipurchasing idecisions ifor iSAM iCipondoh imeatballs iat iCV.Surya iArtha iMutiara iCipondoh, iIn iTangerang iCity